Circadian Sensitivity of Noise Trauma-Induced Hearing Loss and Tinnitus in Mongolian Gerbils - Grimm, Jannik; Schulze, Holger; Tziridis, Konstantin (Frontiers in Neuroscience, 2022)
Noise induced hearing loss (HL) has a circadian component: In nocturnal mice, hearing thresholds (HT) are significantly stronger affected by acoustic traumata when it was given during the night compared to rather mild effects on hearing when applied during daytime. Here we investigate whether such effects are also present in diurnal Mongolian gerbils and determined whether trauma-induced HL correlated with the development of a tinnitus percept in these animals. In particular, we investigate effects of acoustic traumata (2 kHz, 115 dB SPL, 75 min) applied either at 9 AM, 1 PM, 5 PM or 12 PM on HT and tinnitus development in 34 male gerbils. HT were measured by acoustic brainstem response audiometry at defined times one day before and one week after the trauma. Possible tinnitus percepts were assessed behaviorally by the gap prepulse inhibition of the acoustic startle response at defined times one day before and one week after the trauma. We find daytime dependent changes due to trauma in mean HT in a frequency dependent manner comparable to the results in mice, but temporally shifted according to respective activity profiles. Additionally, we found linear correlations of these threshold changes with the strength of the tinnitus percept, with most prominent correlations in the 5 PM trauma group. Taken together, circadian sensitivity of the HT to noise trauma can also be found in gerbils, and tinnitus strength correlates most strongly with HL only when the trauma is applied at the most sensitive times which seem to be the evening.